Implementation of Mutual Cooperation and Independent Character Education through a Case Study of Fifth-Grade Students - Yoga Adi Pratama; Eko Handoyo; Muh. Sholeh (The Journal of Educational Development, 2025)
Character education represents a central pillar of national education that supports the development of morally responsible and socially competent learners. The present study analyzes the implementation of mutual cooperation and independent character education within the domain of the Pancasila Student Profile among fifth-grade elementary school students. A qualitative phenomenological approach was employed to explore naturally occurring educational practices in classroom and school environments. Primary data were collected through interviews with fifth-grade teachers, school principals, and students, while supporting data were obtained through observation and documentation. Findings indicate that mutual cooperation and independent character education were implemented through collaborative learning activities, group projects, and extracurricular programs designed to strengthen student participation and responsibility. Interview results revealed that collaborative interaction and social concern among students remained inconsistent, while independent learning behavior still required improvement because several students depended on peers or parental assistance during task completion. Structured character-based activities demonstrate potential to strengthen cooperation and independence values, although implementation challenges remain. Continuous evaluation and collaborative support from teachers, school leaders, and families are required to optimize the effectiveness of character education within the Pancasila Student Profile framework.